Evaluasi Kebijakan Pelayanan Terpadu Satu Pintu (Studi pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Tenggara) - Sry Mayunita (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
This study aims to analyze and describe the evaluation of the One-Stop Integrated Service policy at the Investment and One-Stop Integrated Service Office of Southeast Sulawesi Province. This study uses a qualitative research with a descriptive approach. The data collection techniques used are observation, interviews, and documentation. The research informants were 10 people and were determined purposively and consisted of leaders, staff and the community who had taken care of licensing. The results of the study show that: 1) the evaluation of the results shows that the DPMP-PTSP policy in Southeast Sulawesi Province has not been maximized, this is evidenced by the mismatch of existing human resources both in quality and quantity, 2) process evaluation has shown good results, it can be seen from the structuring the authority from the Governor to the DPM-PTSP, the establishment of an implementation team, until the availability of Standard Operating Procedures (SOP) to support the policy implementation process, 3) the impact evaluation has also shown quite good results, although the evaluation carried out is still limited to the target group.